Collaborative gaming: When principals and agents agree to game the system. (8th February 2021) - Pierre, Jon; de Fine Licht, Jenny
Abstract: This paper presents a previously unexplored type of gaming of performance data, collaborative gaming, where the performance measurement system incentivizes the executive and an agency to game collaboratively. The paper shows how overlapping incentives between government departments and agencies to present successful implementation of programs can drive collaboration to modify performance targets and/or performance measurements. The argument is illustrated by two brief case studies of collaboration between the Swedish Department of Employment and the Swedish Public Employment Service in the implementation of labor‐market programs.